New Public Management Reforms and the Performance of Public Enterprises: An Assessment of Privatization in Nigeria's Telecommunications Sector - Adejuwon, David; Amodu, Akeem; Majekodunmi, Aderonke (African Journal of Politics and Administrative Studies, 2024)
The implementation of New Public Management (NPM) reforms, particularly privatization, has been a significant strategy adopted by governments worldwide to enhance the performance of public enterprises. This article focuses on the telecommunications sector in Nigeria, where privatization was introduced as part of broader economic reforms in the early 2000s. The objective is to assess the influence of privatization on the performance of public enterprises within this sector. The article is anchored on public choice theory. It is qualitative in nature, relying on secondary sources of data, such as, journals, textbooks, official publications and internet materials. It observes that privatization of public enterprises in the telecommunication sector in Nigeria has led to improvements in operational efficiency, increased investment inflows, and expanded service coverage. However, challenges such as regulatory effectiveness, equity in service provision, and the socio-economic impact on marginalized populations remain significant concerns. It contributes to the broader discourse on NPM reforms by providing empirical insights into the complexities and outcomes of privatization within Nigeria's telecommunications sector. It concludes with policy recommendations aimed at optimizing the benefits of privatization while addressing its associated challenges to ensure sustainable and inclusive growth in the sector.
Keywords: New Public Management; Operational Efficiency; Privatisation; Public Enterprises; Public Sector Performance; Service Delivery

SME contractors’ management practices to achieve sustainable business performance in the Eastern Cape province, South Africa - Sogaxa, Athenkosi (Acta Structilia, 2024)
The construction industry in the Eastern Cape province of South Africa plays a crucial role in the region’s economy, yet small and medium enterprise (SME) construction companies face significant challenges in achieving long-term business sustainability. This article aims to provide practical guidelines for SMEs, by investigating the most critical construction management practices adopted by SME contractors. Utilising a quantitative approach, data were collected from 59 purposefully selected participants, including directors, construction managers, quantity surveyors, site agents, and technicians, all registered under the Construction Industry Development Board (CIDB) Grades 1-4 in General Building (GB). The management practices of SME contractors were analysed using the relative importance index (RII) and factor analysis to rank these practices according to their significance. Findings indicate that SME contractors prioritise health and safety strategies, effective resource utilisation, integrated project management systems, competent recruitment, strong leadership skills, and robust health and safety management as essential practices. The principal component analysis identified six key management factors to enhance competitiveness while contributing to the region’s sustainable development goals. These factors include shared knowledge among management, effective project scope planning, comprehensive health and safety management, ownership of construction business knowledge, scope control on projects, and clearly defined goals for management teams. This study is original in its focus on the specific management practices that can strengthen the sustainability of SME contractors within a developing region, providing a valuable framework for enhancing their operational effectiveness.

Digital Vulnerability and the Formulation of Harmonised Rules for Algorithmic Contracts: A Two-Sided Interplay - Rodriguez, Teresa de Las Heras Ballell (The New Shapes of Digital Vulnerability in European Private Law, 2024)
This book provides an analysis on whether and how the current European legal framework adequately deals with personal conditions in which digital...

Termination of the Mandate of an Agent: An Examination under OHADA Uniform Act on General Commercial Law - Ndekwena Noh, Alison (Scholars International Journal of Law Crime and Justice, 2024)
When an agency relationship is created, it confers on the parties obligations which must be fulfilled by the parties. These obligations do not remain forever as they can come to an end. This can be done under normal circumstances by the act of the parties or by operation of the law and when the conduct of the agent is in contradiction to the mandate agreement as may be the case if the agent is liable for serious misconduct as provided by the OHADA Uniform Act on General Commercial Law. The provisions of the act regarding termination on grounds of serious misconduct is worrisome, as the act talks about termination in such manner only for commercial agents and is silent about the other two types of agents: the broker and the commission agent. The act also, does not tell us what this serious misconduct it mentions by the commercial agent is, nor gives us insights on what constitutes such conduct to warrant termination of the mandate of the agent by the principal. When termination of the agency is done under conditions as such, it has grave consequences on the agent who might not be entitled to certain benefits associated with termination of the contract such as loss of the right to compensatory allowance or indemnity and more importantly may give room to arbitrary or wrongful termination of the mandate of the agent. Through analytical and comparative studies, this paper focuses on termination of the mandate of an agent under the OHADA Uniform Act on General Commercial Law, wherein, the different modes of termination of the mandate of an agent have been discussed, and more specifically makes an attempt in looking at what serious misconduct is and what could amount to such conduct so as to avoid arbitrary or wrongful termination. It is therefore suggested that, statutory guidelines found in other statutes in relation to the subject matter can serve as a lamp light in our context.
Keywords: Mandate

Editorial on Doing business in Africa: Navigating opportunities and challenges in Africa's emerging markets - Adomako, Samuel; Shenkar, Oded; Liu, Xiaohui; Amankwah-Amoah, Joseph; Ahsan, Mujtaba (Journal of International Management, 2024)
This editorial delves into the evolving context of doing business in Africa, tracing its journey from being dubbed the “hopeless continent” to becoming a beacon of hope and opportunity. Drawing on a wealth of scholarly research, it highlights Africa's increasing attractiveness for global investments, underscored by rising FDI inflows and the emergence of a vibrant middle class. Despite these promising trends, the editorial also sheds light on the persistent challenges, including institutional fragility and political instability, coupled with limited representation in the existing international business discourse. We advance a more nuanced understanding of Africa's business environment, emphasizing the need for responsible growth, improved governance, and sustainable development. Thus, the Special Issue offers insights into the complexities and challenges of doing business in Africa, as well as the paradoxes and potential for fostering competitiveness and inclusive growth on the global stage.
Keywords: Africa; Doing business; International business; MNEs

Joint and several liability at the interface of national and international law and the FIDIC conditions of contract - Mahasneh, Nisreen (Uniform Law Review, 2024)
The international terms of the 2017 FIDIC Red Book (reprinted and amended in 2022) state that, when the contractor is a joint venture (JV), all members are jointly and severally liable to the employer. These terms also establish certain procedural rules—the most important ones being the submission to the employer of the JV undertaking and the appointment of a leader. However, these international terms do not provide for substantive rules pertaining to the plurality of the JV members. These require reference to the applicable law that governs the construction contract. The applicable law can be domestic law, such as Qatari law, or an international soft law, such as the Unidroit Principles. Comparing these two possibly applicable laws, it becomes evident that there are no significant differences between the two regarding the substantive rules concerning a plurality of obligors. Furthermore, it is argued that the majority of these substantive legal rules, whether national or international, are inoperative in a construction contract incorporating the international terms of the FIDIC Red Book.

Termination of Commercial Sale Contracts under the OHADA Uniform Act Relating to General Commercial Law - Ataíde, Rui; Boura, Marta (Centro de Investigação de Direito Privado (CIDP) Research Paper, 2024)
The Uniform Act relating to General Commercial Law of the Organisation for Harmonisation of Business Law in Africa (hereinafter referred to as the OHADA Uniform Act) establishes a commercial sale regime applicable to any trader (natural or legal person), including any commercial companies whose place of business or registered office is located in the territory of a party to the Treaty on the Harmonisation of Business Law in Africa. In this study we propose to analyse the non-performance of commercial sale agreements, focused on its termination regime, by reflecting on the right of termination, the termination by judicial means, its grounds, exemption from liability and the effects of termination. The economic and legal relevance of the commercial sale contract justifies the opportunity to reflect on how legal standardisation process has been achieved overall, particularly with regard to termination regimes. Both OHADA Uniform Act and the Vienna Convention on Contracts for the International Sale of Goods of 1980 (CISG) were conceived as unification mechanisms to circumvent the constraints and legal uncertainty associated with cross-border trade. Therefore, this analysis aims to assess how OHADA rules embody the long process of evolution in French law, as well as the influence of the CISG.
Keywords: CISG; Commercial sale contracts; Comparative law; French law; International Organisations; Legal standardisation; OHADA; Portuguese law; Termination regime; Uniform Act relating to General Commercial Law for Harmonisation of Business Law in Africa

Sustainable development clauses in international contracts through the lens of the Unidroit principles - Pannebakker, Ekaterina (Uniform Law Review, 2024)
Most transactions that leave an imprint on the environment and communities are organized by commercial contracts. However, little is known about the way in which parties reflect sustainable development in contractual clauses. How can parties to international contracts commit to respect sustainable development goals? What are the possible degrees of commitment? Which contractual mechanisms can apply to the monitoring of compliance? How does one establish a link between the failure to meet sustainable development goals and the contractual liability or termination of contract? This article identifies contractual clauses relating to sustainable development and analyses these clauses through the lens of the 2016 International Institute for the Unification of Private Law (Unidroit) Principles of International Commercial Contracts (PICC). Drawing inspiration from open access contracts, the analysis will demonstrate that Article 1.8 of the PICC, precluding inconsistent behaviour, and Articles 5.1.4 and 5.1.5, on the duty of best efforts and the obligation to achieve a specific result, as well as the provisions on liability, can assist contract drafters, judges, and arbitrators in drafting and interpreting such clauses.

Mobile money and financial inclusion in Africa: Emerging themes, challenges and policy implications - Osabutey, Ellis L. C.; Jackson, Terence (Technological Forecasting and Social Change, 2024)
Mobile money is purported to promote financial inclusion. The growing number of studies have largely focused on transactions and related benefits with limited attention to emerging challenges, policies and initiatives that address the relative needs of different stakeholders. Consequently, little has been done to probe the ‘bottom-of-the-pyramid’ paradigm that underpins these assumptions. There has been inadequate endeavour to examine ways that empirical research could shed more light on these challenges and how to overcome them. To address these gaps, this study reviews the emerging literature on mobile money that explores both benefits and challenges. From our study three main themes emerge that suggest areas where challenges to the efficacy of the mobile money-financial inclusion link still appears not to have been adequately addressed by policymakers: ensuring integrity, privacy and security; addressing resource and infrastructure constraints; and integrating stakeholder benefits. Yet we suggest merely addressing these challenges does not go far enough in safeguarding the needs of local communities, as major stakeholders. Evidence from our study suggests little direct benefit to the poorer sections of local communities, only to the strata above and to elites and external stakeholders. This has implications for development and social change through technology adoption.
Keywords: Africa; Bottom-of-the-pyramid; Financial inclusion; Fintech; Mobile money

Transborder flow of personal data (TDF) in Africa: Stocktaking the ills and gains of a divergently regulated business mechanism - Babalola, Olumide (Computer Law & Security Review, 2024)
Technology-based transactions are inseparable from the routine exchange of data. These exchanges may not pose privacy problems until the movement takes extra-territorial turns thereby facing multiple levels of cross-border regulations. In the 80 s, the frequency of transfer of personal data beyond geographical boundaries in Europe precipitated the regulation of transborder data flows (TDF) beginning with the enactment of the Organization for OECD Guidelines. In Africa, the concept of TDF is more complex than usually viewed by the stakeholders and this is partly because neither the African Union nor other regional bodies have introduced legislation on TDF. Like many concepts in data protection, TDF is bereft of a generally accepted meaning. Regardless of the uncertainty, this paper approaches TDF as the transmission of personal data from one country to another country or international entity for the purpose of processing. The paper discusses some definitions of TDF as understood under African regional and national data protection legislation. In a comparative and normative approach, the paper analyses the barriers to TDF in Africa vis a vis the European experience and then concludes with recommendations for workable TDF within and outside the continent from an African perspective beginning with the harmonization of existing regional framework.
Keywords: Africa; Data Protection; ECOWAS; GDPR; Privacy; Transborder data transfer

Influence of remuneration on organizational performance in co-operative banks in Kiambu, Kenya - Brian, Kasale; Abuga, Isaac Mokono (African Journal of Social Issues, 2024)
This study investigates the influence of remuneration on organizational performance in cooperative banks in Kiambu County, Kenya. Employing a mixed-methods approach, the research explores how compensation packages, salary reviews, and employee recognition impact performance. The study utilizes a descriptive research design with structured questionnaires to gather data from 94 participants. Findings indicate a significant correlation between competitive remuneration and enhanced organizational performance. The majority ofemployees are satisfied with salary increments and recognize the positive effects of frequent salary reviews on their motivation and job satisfaction. The study also highlights the importance of recognition and praise in boosting employee morale and engagement, contributing to overall organizational success. This research is grounded in Equity Theory, which posits that fair treatment in compensation leads to higher motivation and productivity. The conclusions drawn suggest that cooperative banks should implement equitable and competitive remuneration strategies, along with regular salary reviews and robust recognition programs, to enhance performance. The study provides valuable insights for policymakers andbank managers aiming to improve organizational effectiveness through strategic human resource practices.
Keywords: Co-operative Banks; Employee Motivation; Equity Theory; Organizational Performance; Remuneration

Articulation between Soft Law and Hard Law in the Award of Public-Private Partnership Contracts through Unsolicited Bids in Burundi: Towards Harmonization with International Practice - Amani, Jean Pierre (Open Journal of Social Sciences, 2024)
The awarding of public-private partnership (PPP) contracts through unsolicited bids is characterized by flexible domestic law, with the involvement of public and private players aiming to achieve the general interest objective of public infrastructure development and, by extension, national development. These players are helping to build the normative framework for PPP project activities by spontaneous offer, given their increasingly widespread use on the bangs of positive law, while their standards are classically deprived of the binding force attached to hard law. Marked by its normative guarantee, the flexible law of unsolicited bids is situated at the threshold of the mandatory, and is essential to PPP law. It produces legal effects by linking up with the hard law of PPP contracts, which is the law of the parties. This link between soft law and hard law has a major legal impact on the transformation of the law and legal certainty, for the benefit of investment confidence, especially international investment confidence. Faced with the limitations of positive law on the award of PPP contracts in unsolicited bids, and the difficulties of interpreting soft law and hard law standards, there is a need for harmonization with international practice. To this end, the instruments of the United Nations Commission on International Trade Law (UNCITRAL) on PPPs are being used to link up with Burundian hard law through a transposition mechanism. It is therefore possible that our positive approach to PPP contracting could be improved, highlighting the principle of competition and the exception of non-competition, while taking into account the win-win principle, risk sharing and performance. Finally, the article considers the adjustments to the hard law that would be necessary if Burundi were to decide to revisit the legal framework to make it more attractive to investment, and thus ensure the completion and financing of PPP contracts by spontaneous bidding.
Keywords: Articulation of Law; Competition Principles; Hard Law; Harmonization Principles; Legal Certainty; Mutation of Law; Soft law; Spontaneous Offer

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (ICTD Working Paper, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability